Islam and gender: The Bangladesh perspective - Hasan, Md. Mahmudul (Bangladesh Institute of Islamic Thought (BIIT), 2016)
This book contains English essays on gender issues the author Shah Abdul Hannan originally wrote in Bangla over more than two decades. As part of his continuing quest for justice, he has been passionate about establishing gender egalitarianism in Bangladesh society. Even though the sociocultural reality of Bangladesh has been at the back of his mind while penning his thoughts transmitted in these essays, they can be effective in addressing gender disparities in other societies as well. The crux of his arguments with regard to gender issues corresponds with what the emerging Islamic feminist discourse promotes, that is, the best way to address gender inequities and gender based discrimination is to go back to the teachings of Islam. At the same time, Shah Abdul Hannan believes, it is important to understand the primary sources of Islam – the Qur’an and the Sunnah – in the context of contemporary concerns and perspectives. This book should be highly useful to all those who are interested in Islam and gender as well as policy makers and researchers in this field.